Diseño de un plan de negocios para el cultivo, procesamiento y comercialización de cannabis medicinal (2019)
Cannabis has been a plant used by various cultures throughout history, from ancient China to the American continent. Its importance lies in its medicinal properties mainly, to this is added other applications such as the manufacture of paper products, textiles, construction materials, animal beds among others. Unfortunately, due to the use of the plant for illegal purposes, Cannabis is perceived negatively nowadays by a large number of the population.